Strengths and Weaknesses of Emergency Remote Teaching in Higher Education From the Students’ Perspective: The Portuguese Case - Albuquerque, Fábio; dos Santos, Paula G.; Martinho, Carla (Frontiers in Education, 2022)
Motivated by the Covid-19 pandemic, most students of higher education institutions in Portugal experienced online learning from March 2020 to July 2020. Based on the answers by students to a set of two open questions included in a questionnaire, this paper aims to identify the positive (strengths) and negative (weaknesses) aspects of online learning during this period, which is also known as emergency remote teaching. 2,107 valid answers were gathered. Issues related to comfort and time management were the topics most frequently mentioned by students as strengths, particularly for those who are simultaneously workers. On the other hand, the assessments, interaction, and self-confidence comprised the set of the most frequently mentioned by students as weaknesses. In this latter context, the most evident differences were found by age, type of course, and students' status. The breakdown by gender did not show any relevant difference, regardless of the item under analysis. These findings may be useful for decision-makers to plan their actions, particularly regarding the new challenges for the future of higher education programs. Those actions may include the options regarding the most proper learning model among face-to-face, online, or blended learning by case, as well as the measures to improve the overall quality of the online learning to increase the students satisfaction.